Pelatihan Pembuatan Penelitian Tindakan Kelas pada Guru-Guru SD Kecamatan Kota Gajah Lampung Tengah - Nelly Astuti; Frida Destini; Fadhilah Khairani; Ika Wulandari Utamining Tias; Amrina Izzatika (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Classroom Action Research (CAR) is aimed at finding solutions to social problems. CAR is carried out by starting with a systematic study of the problem. The results of this study are then used as the basis for overcoming these problems.  In the process of implementing the plans that have been prepared, then an observation and evaluation is carried out, the results of which are used as input to reflect on what happened at the implementation stage. The results of this reflection process then underlie efforts to improve and refine the next action plan. The above stages are carried out repeatedly and continuously until a quality of success can be achieved.Service activities carried out with the aim of understanding and knowing what and how CAR is and understanding the implementation of CAR and being able to carry it out. The targets are elementary school teachers located in Kotagajah District. The method used is the lecture method, question and answer method, and the method of giving examples. The expected condition after this service is an increase in the understanding and knowledge of teachers about what and how CAR is, what and how to make and implement CAR.